Desenvolvimento e implantação de fab labs: um estudo teórico no contexto das regiões norte e nordeste - Fonseca, Francisco Wesley de Souza (Universidade Federal Rural do Semi-Árido, 2020)
In view of the rise of movements and organizations seeking to promote the democratization of knowledge and access to technology, Fab Labs emerge. Despite an initial idealization aimed exclusively at improving the form of education, they have been gaining more and more space in various sectors of society. Countless academic researches show that their dissemination contributes in a relevant way to social and economic development, at individual or community level. This work aims to present a theoretical and exploratory study under the current configurations of Fab Labs, accredited and assets connected to the world and national networks, with emphasis on the North and Northeast regions. It will be discussed along this work, requirements and procedures necessary to create new laboratories. The diverse range of possibilities offered by the Fab Labs, signals the predisposition for a possible generalization of them throughout the national territory. In the same way that the dissemination of this concept suggests the increase of the incidence of these laboratories turned to the most varied fields of application and exposed to different contexts. In view of this, this work also presents future perspectives for possible implementations of new laboratories in the North and Northeast regions.
Monografia
Keywords: Fab Labs; Tecnologia; Democratização; Norte; Nordeste; Fab Labs; Technology; Democratization; North; Northeast; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA